Using transmission electron microscopy and 3View® to determine collagen fibril size and three-dimensional organization - Starborg, Tobias (Nat Protoc, 2013)
Collagen fibrils are the major tensile element in vertebrate tissues where they occur as ordered bundles in the extracellular matrix. Abnormal fibril assembly and organization results in scarring, fibrosis, poor wound healing and connective tissue diseases. Transmission electron microscopy (TEM) is used to assess formation of the fibrils, predominantly by measuring fibril diameter. Here we describe an enhanced protocol for measuring fibril diameter as well as fibril-volume-fraction, mean fibril length, fibril cross-sectional shape, and fibril 3D organization that are also major determinants of tissue function. Serial section TEM (ssTEM) has been used to visualize fibril 3D-organization in vivo. However, serial block face-scanning electron microscopy (SBF-SEM) has emerged as a time-efficient alternative to ssTEM. The protocol described below is suitable for preparing tissues for TEM and SBF-SEM (by 3View®). We demonstrate the power of 3View® for studying collagen fibril organization in vivo and show how to find and track individual fibrils. Time scale: ~8 days from isolating the tissue to having a 3D image stack.